Elevated glucose and angiotensin II increase 12-lipoxygenase activity and expression in porcine aortic smooth muscle cells. - Natarajan, R (1993)
The lipoxygenase (LO) pathway of arachidonate metabolism has been suggested to play a key role in atherosclerosis and in mediating several actions of angiotensin II (AII). However, the relationship between LO activation and factors linked to accelerated diabetic vascular disease such as hyperglycemia and AII is not known. We have investigated the effect of high glucose (HG; 25 mM) and AII on LO activity as well as LO protein and mRNA expression in porcine aortic vascular smooth muscle cells (PVSMCs). We observed that cells cultured in HG had significantly higher levels of the cell-associated LO products 12- and 15-hydroxyeicosatetraenoic acids (HETEs). AII added to cells grown in HG specifically further increased only cell-associated 12-HETE levels. Using immunoblot analysis and reverse transcriptase PCRs, we demonstrated the presence in PVSMCs of porcine leukocyte-type 12-LO protein and mRNA, respectively. Furthermore, the levels of both were markedly upregulated by AII as well as by HG. These studies suggest that enhanced 12-LO activity and expression are mechanisms for accelerated vascular disease produced by HG and AII in diabetes mellitus.